The Influence of Principal Academic Supervision and Work Environment on Teacher Performance at State Vocational Schools in Kayuagung District - Ria Octarina; Syarwani Ahmad; Suherman Suherman (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to determine the effect of principal academic supervision and work environment on teacher performance at SMK Negeri Sekecamatan Kayuagung. This study uses a quantitative approach with a survey method. The sample in this study consisted of 50 teachers who were randomly selected at SMK Negeri Sekecamatan Kayuagung. Data were collected through a questionnaire that had been tested for validity and reliability. Data analysis used multiple linear regression to test the effect of independent variables on teacher performance as the dependent variable. The results showed that the principal's academic supervision had a positive and significant effect on teacher performance, as well as the work environment which also had a positive effect on teacher performance. Simultaneously, both independent variables had a significant effect on improving teacher performance. This study suggests the need for improvements in academic supervision and improving the quality of the work environment to support improved teacher performance at SMK Negeri Sekecamatan Kayuagung.